CREATIVE INDUSTRY DEVELOPMENT BASED ON ENTREPRENEURSHIP TRAINING IN DEVELOPING LOCAL ECONOMY IN PAREPARE CITY - Muhammad Rakib; Muchtar Yunus; Nur Amin (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
This study aims to determine the development of creative industries, the usefulness of the implementation of entrepreneurship training, the factors that support and inhibit, and formulate a creative industry development strategy based on entrepreneurship training in an effort to develop local economic areas in the city of Parepare. This research is a type of evaluation research using a qualitative approach. This research was conducted in Parepare Town of South Sulawesi. The subjects of the study were the participants of entrepreneurship training in Kota Parepare, and the Department of Manpower of Parepare City as the manager and implementer of training through UPTD BLK Kota Parepare. Data collection techniques used are Document study, observation, and interview. Data analysis techniques include: (a) Data processing, which consists of categorization and data reduction, (b) data presentation, (c) data interpretation, and (d) drawing conclusions/verifications. The results show that (1) The development of creative industries through entrepreneurship training includes: Information and Communication Technology, Garment Apparel, Beauty, Building, Electrical Engineering, Electronic Engineering, Refrigeration, Manufacturing Engineering, and Welding Technique; (2) The usefulness of the implementation of entrepreneurship training that can shorten the learning period, improve business performance, establish attitudes, help solve business operational problems, prepare entrepreneurs to acquire expertise in certain fields, and produce output that has the ability and knowledge that qualified (3) There are several factors that support and hinder the development of creative industries through entrepreneurship training in developing creative industries, both internal and external factors, and (4) development strategy based creative industry entrepreneurship in an effort to develop the local economy of recruitment and selection of trainees, selection of training instructors, the provision of facilities and infrastructure, curriculum development, and the provision of funds or training budgets.